AGROTOURISM DEVELOPMENT: COMMUNITY-BASED TOURISM IN KARO REGENCY - Theodora Ginting Munthe; Zulkarnain Lubis; Yusniar Lubis (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Sebraya village, located in Karo Regency, has 5.5 ha of agricultural land and livestock that is managed directly by the local villagers. This agricultural land includes fruits, vegetables, diverse types of flowers, medicinal plants, etc. Moreover, this village also has animal husbandry such as sheep, chicken, fish, and pigeon cultivation. This study attempts to examine what agrotourism activities can be explored, what extent agrotourism has been developed, and how the villagers contribute to agrotourism activities. Qualitative method was used in this study. Data collection was conducted by observation, interviews, and documentation. The primary data sources were obtained from the villagers who work in agriculture and the secondary data sources were directly collected by researchers as support data to the first source. The findings revealed that the agrotourism of Seebraya Village could potentially be developed as agrotourism. Yet, the local villagers really needed assistance in the field of planning, counseling about the concept of agrotourism, and facilities that support the development and management of agrotourism in Seberaya Village.